Les résiliogrammes pour représenter la résilience : cas des territoires de la Charente-Maritime et de la Somme face au risque de submersion marine - Elie Chevillot-Miot (VertigO, 2020)
The study aims to highlight performed resiliency process compared to semantic analysis of resiliency concept based on literature. Resiliency definition depends on fields and opinions. This study focuses on resiliency at short and long term towards major marine flooding events on exposed and vulnerable territories: Charente-Maritime and Somme, in order to study and compare resiliency capacities. These feedbacks allow to understand resiliency factors, mechanisms, processes through a graphical representation called “resiliogram”. The method rests on semi-guiding surveys conducted on field workers, professional and institutional organisms contributing to the territory dynamism. These interviews permit to obtain the actors’ speeches according to their past, their perception, and information sharing concerning the risk and know-how during a crisis. Multiple capacities constitute the resiliency process. However, these capacities face different temporalities, spatialities leading to mutltidimensional conflicts. The gap between performed and semantic resiliencies increases leading to a partial and anachronistic global risks management, especially regarding climate changes.